2000
DOI: 10.7589/0090-3558-36.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Findings of a Newly Recognized Disease of Elephants Caused by Endotheliotropic Herpesviruses

Abstract: The unique clinical and pathological findings in nine Asian (Elephas maximus) and two African (Loxodonta africana) elephants from North American Zoos with a highly fatal disease caused by novel endotheliotropic herpesviruses are described. Identification of the viruses by molecular techniques and some epidemiological aspects of the disease were previously reported. Consensus primer polymerase chain reaction (PCR) combined with sequencing yielded molecular evidence that confirmed the presence of two novel but r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
69
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 9 publications
4
69
1
1
Order By: Relevance
“…Because EEHV1A and EEHV1B have been by far the most predominant causative agents of fatal disease in Asian elephants, the focus for this scenario has obviously fallen onto those two virus types in particular. Provocative early PCR evidence suggested that EEHV1A may be present in skin lesions in healthy wild African adult elephants (1,32). However, we have not been able to confirm that result from further evaluation of archival African skin nodule specimens, and no other examples of EEHV1 in African elephants have been found.…”
Section: Discussioncontrasting
confidence: 46%
“…Because EEHV1A and EEHV1B have been by far the most predominant causative agents of fatal disease in Asian elephants, the focus for this scenario has obviously fallen onto those two virus types in particular. Provocative early PCR evidence suggested that EEHV1A may be present in skin lesions in healthy wild African adult elephants (1,32). However, we have not been able to confirm that result from further evaluation of archival African skin nodule specimens, and no other examples of EEHV1 in African elephants have been found.…”
Section: Discussioncontrasting
confidence: 46%
“…However, other distinct endotheliotropic herpesviruses with nucleocapsids of 80-90-nm diameter have recently been described in elephants. 24 Detailed ultrastructural examination of virus in our cases demonstrated enveloped as well as naked cytoplasmic virions and morphologic features characteristic of BHV-4 rather than BAdV. Definitive diagnosis of BHV-4 was possible after PCR results demonstrated characteristic 130-bp bands using BHV-4-specific primers and no bands visible on electrophoretic gels using adenovirus-specific primers.…”
mentioning
confidence: 61%
“…Most were in captive-born Asian calves between 1 and 8 years old, with a major peak between 1 and 4 years of age. Pathological samples, including both peripheral whole blood and all necropsy tissues tested by PCR carry high levels of EEHV DNA (4,10,13,14).…”
mentioning
confidence: 99%
“…The heart, lung, tongue, and most other major internal organs contain typical intranuclear herpesviruslike inclusion bodies and virions in vascular endothelial cells, which contribute to microvascular damage and focal hemorrhagic lesions (13,14). EEHV infections were also responsible for the deaths of the first Asian elephant calves born at the Bronx Zoo (Bronx, New York, NY) and at the Woodland Park Zoo (Seattle, WA), and the first conceived by artificial insemination in both Europe and North America, as well as the first African elephant calf born at the Oakland Zoo (Oakland, CA).…”
mentioning
confidence: 99%